Analisis Pengaruh Pertumbuhan Ekonomi terhadap Ecological Footprint: Studi Kasus Negara-Negara Anggota APEC - Muhammad Ibrahim Yusuf; Wahyu Widodo (Diponegoro Journal of Economics, 2024)
The economic growth of a country is influenced by the level of consumption in society. An increase in societal consumption impacts environmental degradation. The ecological footprint is used as one of the variables that can illustrate environmental degradation. This study aims to analyze the effect of economic growth, foreign direct investment, population size, and renewable energy consumption on the ecological footprint of 19 APEC member countries during the period 1992-2020. The study employs the fixed effect model (FEM) estimation method with cross-section weights and the coefficient covariance method for cross-section SUR (PSCE). The findings reveal that gross domestic product, population size, and renewable energy consumption have a significant effect on the ecological footprint. On the other hand, foreign direct investment does not have an effect on the ecological footprint variable.